Technostress and Academic Resilience Among First-Year College Students: A Cross-Sectional Study - Gilbert Josafat Fanggidae; Arthur Huwae (Department of Guidance and Counseling, FIP, Undiksha, 2026)
When entering education at the university level, first-year students are usually required to master technology—the use of technology as the main support in learning and facilitating all student academic activities. Over time, this can lead to technology-based stress which then leads to poor academic resilience abilities formed by first-year students. This study aims to prove the relationship between technostress and academic resilience in first-year students. This study used a quantitative method with a cross-sectional bivariate correlational design. A total of 423 first-year students became research participants using the accidental sampling technique. Research measurements used Technostress Creators (α = 0.981) and Academic Resilience Scale-30 (α = 0.982). The results prove that there is a significant negative relationship between technostress and academic resilience in first-year students (r = -0.939 and sig. = 0.000; p<0.01). That is, when there is an increase or decrease in technostress experienced by first-year students, it will be followed simultaneously by a decrease or increase in resilience. These results indicate that universities need to conduct regular mentoring and training related to the use of technology as the main means of learning for first-year students so that they can find the right self-strategy to control technostress on the academic dynamics experienced.